Seasonal repeated sprint ability with change of direction variations in U17 and U20 elite brazilian soccer players: A comparative study - Jorge, G.; Garrafoli, M. T.; Abad, C. C. C. (The Journal of Strength and Conditioning Research, 2020)
This study aimed to describe seasonal variations of repeated sprint with change-of-direction ability in young elite Brazilian soccer players. The Bangsbo sprint test (BST) was performed by 21 under-17 (U17) (176.9 cm; 68.2 kg) and 22 under-20 (U20) athletes (178.7 cm, 74.4 kg) at the start, middle, and end of the season. The fatigue index (FI) was calculated in seconds and in percentage of decrease (%D) for comparisons. Both age categories showed higher BST performance in the middle and end compared with the start of the season (p = 0.05). The U20 players performed better at the start than the U17 players. The U17 soccer players showed higher FI at the start and in the middle in comparison with the U20 players (p = 0.05). They also showed lower FI at the end of the season in comparison with the start and middle of the season (p = 0.05). The U20 players showed significant reductions in the FI in the middle and at the end in comparison with the start of the season (p = 0.05). Only the U17 soccer players showed lower %D at the end in comparison with the start of the season (p = 0.05). To summarize, both U17 and U20 players performed BST poorly at the start, increased the BST performance until the middle, and maintained the BST performance until the end of the season. A difference in the magnitude of enhancement was observed between U17 and U20 soccer players, which was found to be dependent on the initial values. Finally, the mathematical model to calculate the FI requires caution.